PENERAPAN METODE BOYER MOORE UNTUK PENCARIAN STRING PADA APLIKASI PENYEWAAN KENDARAAN BERODA DUA BERBASIS ANDROID - Andreas; Edy, Edy (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2024)
In the modern era, transportation for online vehicle rental has become a necessity in daily activities. However, many people still struggle to find and rent two-wheeled motorized vehicles. To address this, an Android-based application can be created using the Boyer Moore method. This application will make renting two-wheeled motorized vehicles easier and more convenient. It will provide various sorting features such as type, brand, and rental price, allowing tenants to choose the vehicle they want. By connecting the application to the internet, it will also benefit vehicle rental service providers by reaching a wider range of customers and helping people carry out their daily activities more efficiently. Ultimately, this will contribute to Indonesia's economic turnover.